Microscopic and submicroscopic Plasmodium infections in indigenous and non-indigenous communities in Colombia (2020)
ABSTRACT: Background: The indigenous population is considered a highly susceptible group to malaria because individuals usually live in areas with high exposure to Anopheles and poverty, and have limited access to health services. There is a great diversity of indigenous communities in Colombia living in malaria-endemic areas; however, the burden of infection in these populations has not been studied extensively. This study aimed to determine the prevalence of Plasmodium infections in indigenous and non-indigenous communities in two malaria-endemic areas in Colombia. Methods: A community-based cross-sectional survey was conducted in seven villages of Turbo and El Bagre municipalities; three of these villages were indigenous communities. Inhabitants of all ages willing to participate were included. Sociodemographic and clinical data were recorded as well as household information. The parasitological diagnosis was performed by microscopy and nested PCR. The prevalence of microscopy and submicroscopic infection was estimated. An adjusted GEE model was used to explore risk factors associated with the infection. Results: Among 713 participants, 60.7% were from indigenous communities. Plasmodium spp. was detected in 30 subjects (4.2%, CI 95% 2.9-5.9); from those, 29 were in the indigenous population, 47% of infections were afebrile, and most of them submicroscopic (10/14). Microscopic and submicroscopic prevalence was 2.5% (CI 95% 1.6-3.9) and 1.7% (CI 95% 0.9-2.9), respectively. In El Bagre, all infections occurred in indigenous participants (3.9%, CI 95% 2.2-7.1), and 81% were submicroscopic. By contrast, in Turbo, the highest prevalence occurred in indigenous people (11.5%; CI 95%: 7.3-17.5), but 88.8% were microscopic. Living in an indigenous population increased the prevalence of infection compared with a non-indigenous population (PR 19.4; CI 95% 2.3-166.7). Conclusion: There is a high proportion of Plasmodium infection in indigenous communities. A substantial proportion of asymptomatic and submicroscopic carriers were detected. The identification of these infections, not only in indigenous but also in the non-indigenous population, as well as their associated factors, could help to implement specific malaria strategies for each context. Keywords: Asymptomatic infections; Indigenous communities; Malaria; Submicroscopic infections.